Mapping and spatial variability of soil nutrients in farmland of red soil hilly regionat village scale - LU Peng; SU Yi-rong; NIU Zheng; WU Jin-shui (浙江大学学报. 农业与生命科学版)
Taking Wangjiadang village in Taoyuan county of red soil hilly region as an experimental site, random sample approaches were employed for the sampling scenario with 522 spots sampled in topsoil (0-20 cm) by Global Position System (GPS). Geostatistics combined with GIS was used to determine the spatial variability characteristics and compare spatial heterogeneity. The results showed that there were significant differences in ranges of spatial autocorrelation among three soil properties at isotropism, which of soil organic carbon, total N, and total P was 261 m, 208 m, and 133 m respectively. Dimension of soil organic carbon, total N, and total P was 1.874, 1.886, and 1.939 respectively. Spatial distribution pattern of soil organic carbon was similar to that of total N at NE150° direction, and they were distributed apparently in strip. Changes of landscape patterns mainly resulted from terrain change, i.e. the spatial distribution patterns of soil organic carbon and total N exhibited the tread of decreasing gradually from higher areas to lower areas. While soil total P was distributed randomly and its patches characterized trivial and “star-studded”; it did not exhibit symmetry pattern at NE150° direction, which was related to its immobile property. The standard semivariograms of soil nutrients suggested that change of spatial structure of soil nutrients is consistent with that of dimension.